A Casual Analysis in Research on History of Education - Vakhovskyi, Leonid; Ivchenko, Tetiana; Sechka, Svitlana (Journal of Education Culture and Society, 2022)
Aim. The purpose of the study is to reveal the cognitive potential and limitations of causal analysis in historical and pedagogical research and to consider alternative methods of explaining historical and pedagogical facts. Methods. Methodological significance for the study were the principles of historicism, objectivity, historiographical tradition, taking into account the totality of facts. To implement the goal a set of theoretical methods was used: analysis, synthesis, comparison, generalisation, and systematisation of scientific positions, historical-genetic, historical-comparative, historical actualisation of the problem. Results. The essence of causality as one of the most important forms of interconnection and interdependence of phenomena and processes of being, expressing a special genetic relationship between them, reveals the specificity of functional and stochastic (random) causality. Historical forms of determinism were characterised: classical (linear), non-classical (non-linear) and neoclassical (fractal). Conclusion. The search for monocausal determination in the study of historical and pedagogical processes seems unproductive. To get a more complete and reliable picture of the cause-effect relations the causal analysis should be complemented by teleological analysis, which will make it possible to find out not only why, but also for what purpose certain actions were carried out. Only in this case is it possible to provide scientific and objective historical explanations and interpretations, the adequacy of understanding of historical and pedagogical facts, to find ideas and meanings in the past experience, which will help to solve contemporary educational problems, to predict the development of education in the future.